Platelet and Fibrinogen Survival in Calves Implanted with Artificial Heart and Ventricular Assist Device -Correlation with Autopsy Findings - Al-Mondhiry, Hamid; Pae, Walter E; Miller, Cynthia A; Pierce, William S (Thrombosis and Haemostasis, 1992)
The two main ingredients of blood clots formed on artificial surface are platelets and fibrinogen. In this study, we measured platelet and fibrinogen survival in calves implanted with total artificial heart (TAH) and left ventricular assist device (LVAD), and correlate these data with autopsy findings. Platelet survival with autologous 111In-labeled platelets was performed on nine calves implanted with TAH and five with LVAD. Fibrinogen survival with 131I-labeled homologous fibrinogen was performed on six calves with TAH and three with LVAD. Platelet survival was significantly shortened in both groups of animals: 5.89 ± 0.52 days, control 6.46 ± 0.31 days, p = 0.0013; fibrinogen survival was normal: 8.79 ± 1.20 days, control 8.64 ± 1.16 days. At autopsy two calves with TAH had multiorgan thromboembolism. Two other animals with TAH and four with LVAD had focal renal infarcts. Most animals had minor clot formation within the prosthetic device. Major septic complications occurred in four calves with TAH and one with LVAD. Continuous platelet activation by artificial surface probably explains the shortened platelet survival and thromboembolic complications.